The Relationship of Mental Health Literacy to Help-Seeking Behavior: Systematic Review - Endro Dwi Iswanto; Dian Ayubi (Journal of Social Research, 2023)
Mental health is an important aspect in realizing overall health. It is estimated that one in four people will suffer from a mental disorder during their lifetime. There are approximately 450 million people suffering from mental and behavioral disorders worldwide where about 85% of people with severe mental disorders in developing countries do not receive treatment for their disorders. This study aims to determine the relationship between mental health literacy and help-seeking behaviors. This research method uses Systematic review to search for articles on several data based including: PubMed, EBSCO, Science Direct, ProQuest, Taylor & Francis, Scopus, and Google Scholar. Search results obtained with the keywords Mental health literacy, mental health, help-seeking behavior obtained 539 articles. After being filtered based on inclusion criteria, namely research articles relevant to the purpose of writing, free full-text, English or Indonesian, respondents' age of 15 years, and published in 2018-2022 produced 62 articles. The same article, not the result of a research or³ review article, and different articles of targets and variables were issued so that 10 articles were obtained. The result of this study is that there is a significant relationship between mental health literacy and help-seeking behaviors. The relationship of mental health literacy to help-seeking behaviors is positive meaning that an increase in scores on mental health literacy also affects an increase in scores on help-seeking behaviors. It can be concluded that the higher the level of mental health literacy, the more it can improve help-seeking behavior.